Dataset on the Number of Schools, Teachers, and Students in Sulawesi, Indonesia: Kindergarten, Primary, Junior, Senior High, Vocational, and Islamic Boarding Schools with Educational Access, Quality, and Cultural Implications to Solve Challenges and Strategies in Education Management and Support Sustainable Development Goals (SDGs) - Amirullah Abduh; Sitti Fatimah Achmad; Chaidir Syam; Sulaeman Samad; Muhammad Arham; Mustafa Mustafa; Abdullah Pandang (Bumi Publikasi Nusantara, 2026)
This study presents a dataset on schools, teachers, and students in Sulawesi, Indonesia, covering kindergarten, primary, junior, senior high, and Islamic boarding schools. Using a descriptive mixed approach that combines statistical data, interviews, focus group discussions, observations, and document reviews, the study examines educational access, quality, governance, and cultural dimensions. Findings reveal disparities in enrollment across school levels, unequal teacher distribution between urban and rural areas, and limited cultural integration in curricula. Some levels showed participation gaps, while community involvement in school management remained weak. The dataset emphasizes the need for equitable teacher deployment, culturally responsive pedagogy, and community-based governance to support sustainable education reform and the achievement of Sustainable Development Goals.